2021 9th European Workshop on Visual Information Processing (EUVIP) 2021
DOI: 10.1109/euvip50544.2021.9484062
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Human Action Detection Using a Cascade of Deep Learning Models

Abstract: Human actions that do not conform to usual behavior are considered as anomalous and such actors are called anomalous entities. Detection of anomalous entities using visual data is a challenging problem in computer vision. This paper presents a new approach to detect anomalous entities in complex situations of examination halls. The proposed method uses a cascade of deep convolutional neural network models. In the first stage, we apply a pretrained model of human pose estimation on frames of videos to extract k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Ullah et al [37] introduced a Convolution-Block-Attention-based LSTM model that enhances spatial information accuracy. Riaz et al [38] combined human posture estimation with a densely connected fully Convolutional Neural Network (CNN) for anomaly identification. Hasan et al [1] utilized a recurrent neural net-work (RNN) and a convolutional autoencoder for anomaly detection, while Liu et al [39] integrated temporal and spatial detectors for anomaly identification.…”
Section: Related Workmentioning
confidence: 99%
“…Ullah et al [37] introduced a Convolution-Block-Attention-based LSTM model that enhances spatial information accuracy. Riaz et al [38] combined human posture estimation with a densely connected fully Convolutional Neural Network (CNN) for anomaly identification. Hasan et al [1] utilized a recurrent neural net-work (RNN) and a convolutional autoencoder for anomaly detection, while Liu et al [39] integrated temporal and spatial detectors for anomaly identification.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, they develop a method based on ensemble for identifying regular and aberrant expression of gene patterns by employing traditional cluster algorithms as well as principal component analysis (PCA). Riaz et al [21] suggested deep ensemble-based methods for anomaly detection in complicated scenarios. Furthermore, to identify human being joints, a position-based estimation technique is integrated.…”
Section: Conventional Feature-based Approachesmentioning
confidence: 99%
“…The model proposed can identify anomalies in an occluded environment at a low computational cost. H. Riaz et al [16] detect unusual behavior of candidates in examination halls by cascading deep CNN models. The methodology uses the OpenPose algorithm to extract key body points, which are further used to retrieve patches.…”
Section: Related Workmentioning
confidence: 99%
“…Fatemah and Mahdi [8], A.B. Sargano et al [10], Donahue et al [7], Kanagaraj and Priya [11], Guillermo A. et al [12], H Riaz et al [16], and Ruchi and Manish [17] have taken advantage of various deep neural architectures to encode action dynamics in accordance with human behavior.…”
Section: Introductionmentioning
confidence: 99%